2017
DOI: 10.3389/fmicb.2017.00294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of M75 Streptococcus pyogenes Strains Harboring slaA Gene in Patients Affected by Pediatric Obstructive Sleep Apnea Syndrome in Central Italy

Abstract: Recently we reported an association between pediatric obstructive sleep apnea syndrome (OSAS) and Group A streptococcus (GAS) sub-acute chronic tonsil colonization. We showed that GAS may contribute to tonsil hyperplasia via a streptolysin O (SLO)-dependent cysteinyl leukotrienes (CysLTs) production, which can trigger T and B cell proliferation. In the present study, we characterized the GAS strains isolated from pediatric OSAS patients in comparison with a panel of age and sex matched GAS strains unrelated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…CysLTs activated primary T and B cell proliferation in vitro, which might mediate the development of tonsil hypertrophy and thus, pediatric OSAS. A second study by the same authors identified the GAS virulence factor SlaA, which is reported to target the CysLT production pathway to also be associated with OSAS . The slaA gene was found in 45.5% of GAS strains isolated from OSAS patients.…”
Section: Complications Arising From Gas Pharyngitismentioning
confidence: 96%
See 1 more Smart Citation
“…CysLTs activated primary T and B cell proliferation in vitro, which might mediate the development of tonsil hypertrophy and thus, pediatric OSAS. A second study by the same authors identified the GAS virulence factor SlaA, which is reported to target the CysLT production pathway to also be associated with OSAS . The slaA gene was found in 45.5% of GAS strains isolated from OSAS patients.…”
Section: Complications Arising From Gas Pharyngitismentioning
confidence: 96%
“…A second study by the same authors identified the GAS virulence factor SlaA, which is reported to target the CysLT production pathway to also be associated with OSAS. 178 The slaA gene was found in 45.5% of GAS strains isolated from OSAS patients. SlaA cleaves the fatty acids palmitic and oleic acids to release arachidonic acid, which is then converted to leukotrienes and CysLTs by the 5-lipoxygenase pathway and may contribute to tonsil hypertrophy and thus, OSAS.…”
Section: Adenotonsillar Hypertrophy and Pediatric Sleep Apneamentioning
confidence: 99%
“…The adenoids are now considered to be a pathogen reservoir, as evidenced by the presence of group A streptococcus, Haemophilus influenzae, Streptococcus pneumoniae, Staphylococcus aureus, Moraxella catarrhalis, and Neisseria meningitidis. [12][13][14] Because the oral cavity and adenoids are structurally adjacent, the oral microbiota in pediatric OSA may be altered.…”
Section: Scientific Investigationsmentioning
confidence: 99%
“…Generally, AMPs are considered to form transmembrane pores, including carpet, barrel-stave, and toroidal pore-type models when the peptides reach a concentration threshold on the cell membrane (Gaspar et al, 2013). As showed in Figure 2D, PPV1 could extensively interact with the acyl region of the phospholipids to disintegrate bacterial cell membrane (Raja et al, 2013).…”
Section: Discussionmentioning
confidence: 99%